(untitled) (ModaPalavra e-periódico, 2019)
The communication strategies applied by the apparel and accessories popular brands to repositioning as Fashion brands are addresses in this paper. The goal is to propose a systematization of the series of strategies used in the public communication of the brands C&A, Lojas Renner, Marisa and Riachuelo. The study presents part of the results of a qualitative research, with exploratory and descriptive goals, based on documentary sources in the internet. As results, the strategies, actions, resources and speeches used by the popular brands can by systematized in three basic strategies: (1) fast fashion system; (2) co-branding and association with the fashion system; and (3) investment in special stores. Each basic strategy is supported by a series of complementary actions that, in interaction, promote the association of the popular brands with the Fashion culture.